2016
DOI: 10.1111/trf.13947
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Factor XIII inhibitor associated with mantle cell lymphoma

Abstract: This is the first reported case of an acquired FXIII inhibitor associated with mantle cell lymphoma in which the epitope specificity of the pathologic autoantibody was accurately defined. Antifibrinolytic therapy played a prominent role in the prevention of bleeding complications in the window period between initiation of immunosuppression and disappearance of the pathologic anti-FXIII autoantibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Many previously published studies reported acquired coagulation inhibitors accompanying lymphoma, mostly acquired hemophilia A or factor VIII inhibitors. [15][16][17][18][19][20] Similarly, acquired factor X deficiencies or inhibitors showed association with lymphoproliferative diseases via three mechanisms. 7,21 The most prevalent mechanism was amyloid fibril absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Many previously published studies reported acquired coagulation inhibitors accompanying lymphoma, mostly acquired hemophilia A or factor VIII inhibitors. [15][16][17][18][19][20] Similarly, acquired factor X deficiencies or inhibitors showed association with lymphoproliferative diseases via three mechanisms. 7,21 The most prevalent mechanism was amyloid fibril absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Paraneoplastic manifestations of lymphoma include hematologic abnormalities and neurological deficits [ 1 ]. As summarized in Table 1 , paraneoplastic coagulopathies have rarely been reported in the setting of systemic involvement by lymphoma [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. We report the first case of a paraneoplastic coagulopathy in isolated primary central nervous system lymphoma (PCNSL).…”
Section: Tablementioning
confidence: 99%
“…The erythroblast count is a percentage of leukocyte count In this case series, cancer treatment allowed FXIII recovery. Acquired FXIII deficiency has also been described in several lymphoid pathologies including monoclonal gammopathy of undetermined significance, 6 mantle cell lymphoma, 7 and lymphoblastic leukemia. 8 These deficiencies are related to the presence of an antibody directed against FXIII that accelerates FXIII clearance and reduces FXIII activity.…”
Section: Induction Treatment Was Started By Elam02 Protocol (Nct00149162) Remission Was Achieved With No Erythroblastsmentioning
confidence: 99%